PERANAN VISUM ET REPERTUM TERHADAP KEJAHATAN KESUSILAAN PEMERKOSAAN - Eka Pratama, Muhammad Rizky (Peneliti.net, 2024)
A criminal act is a series of actions committed by a person or persons that have legal consequences for the perpetrator. One of the criminal acts contained in Indonesian positive law is a crime of decency (rape). The perpetrator can be one or more people. The research method used is a normative juridical research method with secondary data resources. The results of the study indicate that to uncover a criminal act of rape, it is necessary to have an examination by law enforcement without compromising the rights of the perpetrator and not ignoring the victim's sense of justice. One of the victims' sense of justice that should not be ignored is the disclosure of violence. This is because in the visum et repertum, this element of intercourse can still be proven and explained in it even though the occurrence of the crime of rape has been going on for a long time from the report of the crime. However, for signs of violence on rape victims, this may not be contained in the visum et repertum, considering that signs of violence which are usually in the form of wounds on the victim's body can gradually recover and disappear with increasing time. Thus, the role of visum et repertum can provide clues (corpus delicti) regarding the presence of elements of sexual intercourse and elements of violence, estimate the time of the crime of rape, can also provide results of examination of evidence in the crime of rape.